Mucocele‐like lesions diagnosed on breast core biopsy: Low risk of upgrade and subsequent carcinoma. Issue 3 (11th October 2017) - Zhang, Gloria; Ataya, Dana; L. Lebda, Paulette; Calhoun, Benjamin C.
Abstract: Mucocele‐like lesions of the breast diagnosed on core biopsy are usually excised to exclude the possibility of partial sampling of an invasive mucinous carcinoma. The goal of this study was to correlate the pathologic and radiologic features of mucocele‐like lesions to determine if excision is mandatory. Over a 16 year period we identified 32 patients with mucocele‐like lesions diagnosed on 27 (84%) stereotactic and 5 (16%) ultrasound‐guided core biopsies. The indications for core biopsy were: calcifications in 24 (75%), a mass in 7 (22%), and a mass with calcifications in 1 (3%). There were 22 (69%) mucocele‐like lesions without atypia and 10 (31%) with atypical ductal hyperplasia or detached groups of atypical cells. Of the 22 mucocele‐like lesions without atypia, 19 (86%) were excised: 15/19 (79%) were benign, 3/19 (16%) had atypical ductal hyperplasia and 1/19 (5%) had ductal carcinoma in situ. None of the patients with mucocele‐like lesions without atypia were upgraded to invasive carcinoma. The single patient who was upgraded to low‐grade ductal carcinoma in situ had a history of ductal carcinoma in situ in the same breast. Of the 10 patients with mucocele‐like lesions with atypia, 9 (90%) were excised: 5/9 (56%) were benign, 1/9 (11%) had atypical ductal hyperplasia and 3/9 (33%) had invasive carcinoma. Of the patients with mucocele‐like lesions with atypia who were upgraded to invasive carcinoma, one had a BIRADS 5 mass and discordant pathology and one had a history of Hodgkin lymphoma and mantle radiation. There were 24 patients with mucocele‐like lesions with or without atypia who were not upgraded on excision, and none developed breast cancer after a median of 51 months (range 7‐192). These findings indicate that mucocele‐like lesions without atypia are unlikely to be upgraded on excision and are associated with a low risk for the subsequent development of carcinoma.